A cryptic deletion of 2q35 including part of the PAX3 gene detected by breakpoint mapping in a child with autism and a de novo 2;8 translocation. Issue 6 (1st June 2002) - Borg, I; Squire, M; Menzel, C; Stout, K; Morgan, D; Willatt, L; O'Brien, P C M; Ferguson-Smith, M A; Ropers, H H; Tommerup, N; Kalscheuer, V M; Sargan, D R
Abstract : We report a de novo, apparently balanced (2;8)(q35;q21.2) translocation in a boy with developmental delay and autism. Cross species (colour) paint (Rx) and SKY FISH, forward and reverse chromosome painting, and FISH with subtelomeric probes were used to examine the patient's karyotype, but further rearrangements were not detected. FISH with region specific clones mapping near 2q35 and 8q21.2 breakpoints and STS mapping performed on the isolated derivative chromosomes were used to refine the location of the breakpoints further. A cryptic deletion of between 4.23 and 4.41 Mb in extent and involving at least 13 complete genes or transcription units was found at the breakpoint on 2q35. The deletion includes the promoter and 5` untranslated region of the paired box 3 ( PAX3 ) gene. The child has very mild dystopia canthorum which may be associated with the PAX3 haploinsufficiency. The 8q21.2 breakpoint is within MMP16 which encodes matrix metalloproteinase 16. We postulate that the cryptic deletion and rearrangement are responsible for the patient's phenotype and that a gene (or genes) responsible for autism lies at 2q35 or 8q21.2. The results present a step towards identifying genes predisposing to autism.